Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00406-007-0743-1
|View full text |Cite
|
Sign up to set email alerts
|

Complicated grief after traumatic loss

Abstract: The traumatic loss of an unborn child after TOP due to fetal malformation and/or severe chromosomal disorders in late pregnancy is a major life-event and a potential source of serious psychological problems for those women. To obtain information on the course of grief following a traumatic loss, 62 women who had undergone TOP between the 15th and 32nd gestational week were investigated in a longitudinal study design and compared with 65 women after spontaneous delivery of a full-term healthy child. Grief, post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 21 publications
1
62
0
5
Order By: Relevance
“…The loss of an infant due to stillbirth, miscarriage, neonatal death, or termination on the grounds of fetal abnormalities is recognized as a traumatic life event and can cause parents intensive grief and symptoms of posttraumatic stress [2,3,4]. In particular, women whose pregnancies were terminated after the discovery of fetal malformation or severe chromosomal disorders have been found to experience severe symptoms of posttraumatic stress disorder (PTSD) and prolonged grief even years later [4,5,6]. However, despite the increasing recognition that prenatal loss can lead to psychiatric disorders, few of the women affected receive psychological support [7].…”
Section: Introductionmentioning
confidence: 99%
“…The loss of an infant due to stillbirth, miscarriage, neonatal death, or termination on the grounds of fetal abnormalities is recognized as a traumatic life event and can cause parents intensive grief and symptoms of posttraumatic stress [2,3,4]. In particular, women whose pregnancies were terminated after the discovery of fetal malformation or severe chromosomal disorders have been found to experience severe symptoms of posttraumatic stress disorder (PTSD) and prolonged grief even years later [4,5,6]. However, despite the increasing recognition that prenatal loss can lead to psychiatric disorders, few of the women affected receive psychological support [7].…”
Section: Introductionmentioning
confidence: 99%
“…Termination of pregnancy because of a foetal abnormality is devastating for mothers and their families; most mothers experience significant long-term psychological distress (Cacciatore, 2010;Kersting et al, 2007). Various studies have shown that the death of a baby during pregnancy or shortly after birth triggers long-lasting grief (Badenhorst & Hughes, 2007;Brier, 2008;Kersting et al, 2007) and is associated with high levels of anxiety, depression, and post-traumatic stress symptoms (Badenhorst & Hughes, 2007;Heazell et al, 2016;Hutti, 2005). One report noted that approximately 20% of women experiencing a perinatal loss fulfilled the criteria for post-traumatic stress disorder (PTSD) (Turton, Hughes, Evans, & Fainman, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Anpassungsstö-rungen und akute Belastungsreaktionen sind häufige psychische Störungen, die in kurzem zeitlichen Abstand nach der Totgeburt auftreten können. Im weiteren Verlauf können posttraumatische Belastungsstörungen, persistierende somatoforme Beschwerden oder andere psychische Symptome wie depressive Erkrankungen oder Angsterkrankungen vorherrschen [3,10,14]. Eine Untersuchung von Cougle et al [5] [21,17].…”
Section: Totgeburt -Prävalenz Und Psychische Folgenunclassified